2022
DOI: 10.3390/ma15155361
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Rigid Polyurethane Foam Filled with Sawdust from Primary Wood Processing

Abstract: In this study, the possibility of using sawdust, a by-product of primary wood processing, as a filler (WF) for rigid polyurethane (PUR) foams was investigated. The effects of the addition of 5, 10, 15 and 20% of WF particles to the polyurethane matrix on the foaming process, cell structure and selected physical-mechanical properties such as density, thermal conductivity, dimensional stability, water absorption, brittleness, compressive and bending strengths were evaluated. Based on the results, it was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Członka et al [ 45 ] reported that cracks could be caused by the agglomeration of the fillers. A similar effect was also observed in the research on rigid foams [ 26 ].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Członka et al [ 45 ] reported that cracks could be caused by the agglomeration of the fillers. A similar effect was also observed in the research on rigid foams [ 26 ].…”
Section: Resultssupporting
confidence: 86%
“…Sung and Kim [ 25 ] found that smaller pore sizes resulted in a smaller distance between the cell walls; thus, the resistance to deformation under the external force increased with the decrease in the size of the cells. The addition of fillers to the PUR causes a reduction in cell-wall thickness, which was reflected in the strength test results of the foams [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PUR industry is no exception, and this has encouraged scientists and manufacturers globally to develop and produce composite foams from renewable feedstocks, more specifically isocyanates from fatty/amino acids [ 7 ], polyols from non-edible and edible natural oils [ 8 , 9 ] and natural fillers [ 10 , 11 ]. These natural or bio-based materials reduce greenhouse gas emissions and increase environmental conservation and sustainability, and importantly, are a cost-efficient way to develop and produce PUR composites.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been few studies analysing the impact of fillers on the dimensional stability of bioPUR foams [ 41 , 42 , 43 ] which were synthesised using the system of lower- and higher-functionality polyols. Although the changes in linear dimensions under ambient temperature are not favourable, the sufficient operation in higher temperature and humidity conditions must be validated as well.…”
Section: Resultsmentioning
confidence: 99%